Respuesta :

Answer:

m=-7

Step-by-step explanation:

You begin with the equation:

2m-6=4m+8

The first step of this would be to subtract 2m from both sides. This is the subtraction property of equality.

-6=2m+8

The next step would be to subtract 8 from both sides. This is the subtraction property of equality.

-14=2m

Next, divide both sides by 2. This is the division property of equality.

-7=m

The final step would be the symmetric property of equality.

m=-7

Therefore your proof would have the steps:

subtraction property of equality

subtraction property of equality

division property of equality

symmetric property of equality